Contribution of Particle-Induced Lysosomal Membrane Hyperpolarization to Lysosomal Membrane Permeabilization - Ziglari, Tahereh (Int J Mol Sci, 2021)
Lysosomal membrane permeabilization (LMP) has been proposed to precede nanoparticle-induced macrophage injury and NLRP3 inflammasome activation; however, the underlying mechanism(s) of LMP is unknown. We propose that nanoparticle-induced lysosomal hyperpolarization triggers LMP. In this study, a rapid non-invasive method was used to measure changes in lysosomal membrane potential of murine alveolar macrophages (AM) in response to a series of nanoparticles (ZnO, TiO(2), and CeO(2)). Crystalline SiO(2) (micron-sized) was used as a positive control. Changes in cytosolic potassium were measured using Asante potassium green 2. The results demonstrated that ZnO or SiO(2) hyperpolarized the lysosomal membrane and decreased cytosolic potassium, suggesting increased lysosome permeability to potassium. Time-course experiments revealed that lysosomal hyperpolarization was an early event leading to LMP, NLRP3 activation, and cell death. In contrast, TiO(2)- or valinomycin-treated AM did not cause LMP unless high doses led to lysosomal hyperpolarization. Neither lysosomal hyperpolarization nor LMP was observed in CeO(2)-treated AM. These results suggested that a threshold of lysosomal membrane potential must be exceeded to cause LMP. Furthermore, inhibition of lysosomal hyperpolarization with Bafilomycin A1 blocked LMP and NLRP3 activation, suggesting a causal relation between lysosomal hyperpolarization and LMP.